The effect of strategic flexibility configurations on product innovation - Aydin Beraha; Dursun Bingol; Ela Ozkan-Canbolat; Nina Szczygiel (European Journal of Management and Business Economics (EJM&BE), 2018)
Purpose: The purpose of this paper is to determine the contribution of company functional areas - production, marketing, and human resources - to strategic flexibility configurations. It also seeks to explore the comparative contributions of functional areas to product innovation. Design/methodology/approach: The study uses the fuzzy-set qualitative comparative analysis to develop a better understanding of departmental contributions to strategic flexibility configuration and the effect of strategic flexibility on product innovation by functional areas. Findings: The findings of this study indicate that marketing flexibility has a key role in product innovation. Research limitations/implications: A limited number of cases may be one of the possible reasons for no proven contribution of HR flexibility to product innovation, and may affect results due to poor representation. Practical implications: The required flexibility level is at least the one maintaining the company's status and certifying competitive advantage. Social implications: A pressure for flexibility leads companies to modify their organizational structure, processes, and resources. Originality/value: The environmental change and uncertainty provide dynamic challenges that increase the need of company flexible reactions.
Keywords: 650; Product innovation; Strategic flexibility; Configuration approach; Fuzzy-set qualitative comparative analysis